2011
DOI: 10.1186/1475-2840-10-34
|View full text |Cite
|
Sign up to set email alerts
|

Low serum amylase in association with metabolic syndrome and diabetes: A community-based study

Abstract: BackgroundLow serum amylase levels may reflect impaired exocrine-endocrine relationship in the pancreas. However, few clinical studies have addressed this issue. Therefore, in this epidemiological study, we investigated whether low serum amylase was associated with the pathogenesis of impaired insulin action: metabolic syndrome (MetS) and diabetes.Research Design and MethodsSerum amylase, cardiometabolic risk factors, MetS (Adult Treatment Panel III criteria), and diabetes were examined in 2,425 asymptomatic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 20 publications
9
90
1
2
Order By: Relevance
“…Recent reports indicated that low serum amylase concentrations are associated with increased possibilities for metabolic abnormalities, prevalence of metabolic syndrome, and diabetes. In addition, it can be useful for identifying metabolic syndrome, although further research is needed to understand the mechanism behind these associations (36,39,59).…”
Section: Imprinted Qtl Analysismentioning
confidence: 99%
“…Recent reports indicated that low serum amylase concentrations are associated with increased possibilities for metabolic abnormalities, prevalence of metabolic syndrome, and diabetes. In addition, it can be useful for identifying metabolic syndrome, although further research is needed to understand the mechanism behind these associations (36,39,59).…”
Section: Imprinted Qtl Analysismentioning
confidence: 99%
“…For many years, it has been thought that low serum amylase level reflects diffuse pancreatic damage due to advanced pancreatic disease. But now a days, several studies shown that this low level of serum amylase is also associated with metabolic syndrome and diabetes mellitus 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In epidemiological studies, low serum concentrations of amylase have been associated with elevated BMI (1619), waist circumference (WC) (16,20), or visceral adipose tissue area (21). Furthermore, studies have suggested that AMY1 copy number also plays a role in glucose uptake and glucose metabolism (11,22).…”
Section: Introductionmentioning
confidence: 99%